Analysis for Modulation and Coding Scheme with Data Rate Traffic Over IEEE 802.11AC and 802.11N in Wireless Multimedia - Al-Dulaimi, Aymen Mohammed Khodayer; Al-Dulaimi, Mohammed Khodayer Hassan (International Journal of Computing, 2021)
This paper discusses wireless traffic consisting of various types of data packets. Regardless of the type of data being sent and received, the transmission can suffer from latency problems. The wireless multimedia standard enables the service provider to prioritize voice, video, best-effort, and background data by adding differentiated services code point value to the internet protocol header. This effectively allows network users to benefit from optimal network performance while using various applications with different latency and throughput requirements. In this paper, we conducted a study of five use-cases over two common wireless standards, IEEE 802.11n and IEEE 802.11ac. The study was carried out by prioritizing, respectively, voice, video data packets, with lowest priority assigned to best-effort data packets. The best-effort traffic can have more bandwidth than the voice or video. Under each use case, we evaluated the impact of additional network load on video streaming.